Single-Shot Thoracic Spinal Anesthesia (TSA) In Pediatric Patient Under Laparoscopic Cholecystectomy: A Case Report - Ghozali, Imam; Hamdi, Tasrif; Yusmaidi, Yusmaidi; Sitepu, John Frans (CoinReads Media Prima, 2022)
Introduction: Laparoscopy is mostly performed under general anesthesia (GA) but laparoscopy using anesthesia such as thoracic spinal anesthesia (TSA) is mostly performed by some anesthesiologists and it is very useful when compared to GA. Method: This paper presents a case report of the use of TSA in healthy pediatric patients who administered anesthesia with TSA in the T10-T11 interspace, using 1 ml of hyperbaric Bupivacaine 5 mg/ml mixed with: 1 ml of Levobupivacaine isobaric 5 mg/ml, Fentanyl 50 μg, Ketamine 10 mg and Dexmedetomidine 10 μg mixed in 1 syringe. Results: During procedure, hemodynamically stable, no nausea, vomiting, or discomfort. Postoperative recovery process was very smooth, hemodynamically stable, no pain was reported or PDPH (Post Dural Puncture Headache) even though we used a 26G spinal needle. The use of TSA is considered very practical and more economical even though it is still carried out very carefully. Conclusion: This is only one single case report. TSA can be a better choice compare with general anesthesia. Stable hemodynamic during laparoscope and TSA can avoid systemic effect of general anesthesia like cognitive affect after general anesthesia, longer for recovery from anesthesia, nausea, vomiting, poor control pain and high cost.